A Survey of Methods for Genome Functional Analysis in Comparative Genomics - Udayaraju, P; B. Siva Varma, P; Jeevana Sujitha, M (International Journal of Engineering and Technology, 2018)
In biomedical technologies, Gene functional analysis is an emerging concept in understands the DNA sequence and gene product analysis and gene interaction in different real time medical applications. Finding data sequences of gene functionalities. There are many techniques have been used to progress functionality of functionality of genome analysis. In this paper, we present algorithmic, calculation oriented and mathematical comparison under analysis of genome. We develop techniques for dynamic and automatic calculation of Genome relations; these relations are enabled in automatic identification of orthodox for Genome from redundant Genes in yeast Genome. We present a method to identify automatic protein to protein interaction Based on related patterns related to specific presentations, we observe understand frame of functional proteins were developed to find Gene identification with accurate and reliable formations like sensitivity & specificity. We also present methods for systematic â€œdenovoâ€ identification of motifs. The techniques do not depend on previous information of gene operate and in that way stand out from the present literary works on computational design finding. Based on the genome-wide preservation styles of known elements, we designed three preservation requirements that we used to discover novel motifs. Our comparative results give comparative genomic to process our outstanding of any pieces. Our proposed techniques are flexible to verify comprehensive data genes and provide reliable research on complicated genomes on human specifications. Â Â